ANALISIS KEPERCAYAAN DIRI SISWA PADA PEMBELAJARAN MATEMATIKA DI KELAS IV SD - Astriani, Dea; Soleh, Dudung Amir; Putra, Adi (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2024)
Learning mathematics is often perceived as difficult and affects students' self-confidence. This study is to determine the level of self-confidence, determine the factors and influences of self-confidence, identify effective strategies in increasing student confidence in learning mathematics. This research uses descriptive quantitative method with a sample of class IV SDN Pisangan Baru 07 as many as 47 students. The data collection technique was a questionnaire. The results of the study obtained that self-confidence in learning mathematics has been mostly felt by students. This can be seen from the results of the indicators, namely believing in one's own abilities 66% of the category most, acting independently in making decisions 62% of the category some, having a positive self-concept 49% of the category most, daring to express opinions 49% of the category most. The development of supportive learning strategies is one way to increase student confidence in learning mathematics. Keywords: Self-confidence. Maths learning.